AR Portion: Dynamic solution for visualizing food portions in nutritional tables - Costa, Samuel S. P.; Souza, Ana C. da C.; Miranda, Bianca M. A.; Souza, Alyson M. C. (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR), 2025)
This work proposes the concept of an Android application, based on augmented reality, to make the presentation of nutritional information tables on products interactive and accessible, given that label information is often displayed in reduced sizes, making it difficult to read and understand. The solution overcomes the limitations of physical labels by displaying interesting information based on the portion consumed. Developed with Unity 2022.3.20f1 and ARCore SDK, this application integrates image tracking and surface detection for an enhanced interactive experience.